On the Christian religion - Ficino, Marsilio, 1433-1499 (University of Toronto Press, 2022)
"This is the first translation into English of Marsilio Ficino's De Christiana religione, a text first written in Latin in 1474, the year after its author's ordination in the Roman Catholic Church. On the Christian Religion is this Florentine humanist's attempt to lay out the history of the religion of Christ, the Logos ('Word' or 'Reason'), in accordance with the doctrines of ancient philosophy. The work focuses on how Christ in his pre-incarnate form had been revealed as much to certain ancient pagan sages and prophets as to those of the Old Testament, and how both groups played an equal role in foreshadowing the ultimate fulfillment of all the world's religions in Christianity. The first part elucidates the history of the prisca theologia--the ancient theology--a single natural religion shared by the likes of Zoroaster, Hermes Trismegistus, Orpheus, Aglaophemus, Pythagoras, and Plato, and how it was fulfilled by Christ's incarnation and the spread of his Church through his apostles. The second part of the work, however, constitutes a series of attacks against the ways in which the Old Testament had been variously interpreted by Islamic and, more importantly, Jewish sages who threatened Ficino's own Christological interpretations of Scripture. This new English translation includes an introduction that situates the text within the broader scope of Ficino's intellectual activity and historical context. The book allows us to encounter a more nuanced image of Ficino, that of him as a theologian, historian, and anti-Jewish, anti-Islamic, and anti-pagan polemicist."--